Modeling gas turbine materials’ hot corrosion degradation in combustion environments from H2‐rich syngas - Sumner, Joy; Potter, Andrew; Simms, Nigel J.; Oakey, John (Wiley, 2016)
Components of gas turbines (such as blades, vanes, combustor cans) exposed to combustion environments at high temperature are susceptible to hot corrosion attack. To successfully plan maintenance and to determine whether to operate in novel combustion modes (e.g., in integrated gasification combined cycles that incorporate pre-combustion carbon capture) predictions of hot corrosion component life must be made. In this paper, hot corrosion datasets relating to two alloys, MarM 509 (a cobalt-based superalloy), and Rene 80 (a nickel-based superalloy) form the basis of hot corrosion predictive lifetime models. The model framework is based on the two stages of incubation and propagation, with the transitions from incubation to propagation around the samples being based on Weibull statistics. The impact of a range of temperatures (including 700 and 900 °C), gas compositions (simulating the combustion of natural gas, H2-rich syngas, or partially cleaned syngas), and deposit chemistries/fluxes have been assessed. Predictions have been made including the expected damage spread for a range of different exposure conditions.
Keywords: H2-IGCC; hot corrosion; incubation; lifetime; MarM 509; modeling; propagation; Rene 80; superalloys; Weibull statistics